THE EMBODIMENT OF PERFECTION TO THE LITERARY WORKMANSHIP ON HENRY JAMES’S THE PORTRAIT OF A LADY - sumardjo sumardjo (Faculty of Letters Universitas Balikpapan, 2018)
This study performs the model of the end product of language artist namely Henry James denoting the perfection of craftsmanship equipped with the figure of a lady that behaves far from mere the sheep on the flock. Henry James in The Portrait of a Lady used the exaggeration of the lady’s character to heighten the tension of his mission to search perfection that exhibited something as better or worse than it really is. The shadow of valuing the given character that determined to have an odd choice in her life postulated the congruence within incongruence between what the readers expected and the deed of a lady character. The design of this study initiated with the main theme that is the perfection of workmanship comprising of three sub heading first, the centrality of vision; second, the harmony of a studio life; and the last, the landscape of an American literary tradition. The study operates the aesthetical perspective adopted from Response to Literature by William J. Grace. The conclusion of this aesthetical perspective depicts the dramatic situation of life in which the lady character prefers to confront the will to perfect instead of the will to power in the arena of modern world where the money generally deemed the God.